Potential prognostic parameters and real-world data in patients with primary central nervous system lymphoma: a new brick on the old ones - Ersal, Tuba; Ozkocaman, Vildan; Pınar, İbrahim Ethem; Yalçın, Cumali; Orhan, Bedrettin; Candar, Ömer; Çubukçu, Sinem; Güllü Koca, Tuba; Ali, Rıdvan; Özkalemkaş, Fahir (The European Research Journal, 2023)
Objectives: We aimed to evaluate the potential prognostic factors of patients with primary central nervous system lymphoma (PCNSL). Methods: Thirty-two patients with PCNSL were retrospectively analyzed. Results: All the patients received high doses of methotrexate-based chemotherapy as the first-line treatment. Overall survival was 30.0 ± 7.2 months. Those with partial response and without response had a higher risk of mortality. The increased leukocyte and neutrophil levels were associated with high mortality. Besides, the SIIL as a product of the systemic immune inflammation (SII) and lactate dehydrogenase (LDH); the SIRIL as a product of systemic immune response index (SIRI) and LDH; and the NLL as a product of neutrophil-lymphocyte ratio and LDH were taken into consideration for the first time for the purposes of the present study. Elevated NLL, SIIL, and SIRIL indexes were associated with mortality. Elevated SIIL level, radiotherapy, and partial and no response were the independent predictors of mortality on the basis of the multivariable regression model including the risk factors associated with mortality. Conclusions: SIIL, SIRIL and NLL are prognostic factors in PCNSL. Determining the prognostic factors and risk profile may predict the requirement for more intensive treatment, especially in young patients at high risk.